ABS- Unlocking the opportunities - Preetha Nilayangode; Dinesan Cheruvat; K P Laladhas; Oommen V Oommen (Journal of Traditional and Folk Practices (JTFP), 2016)
Access and Benefit Sharing (ABS) deals with the sharing of benefits arising from the utilization of genetic resources in a fair and equitable way. International Convention on Biological Diversity (CBD) recognizes the rights of countries, through their national governments and has put forth a set of rules and principles governing the use of genetic resources and associated traditional knowledge. In India, the Biological Diversity Act, 2002 and Rules, 2004 governs the access to various biological resources and sharing the benefits accrued. The present paper discusses on various international policies related to ABS, resource mobilization and conservation of bioresearches, operationalization mechanism of ABS, etc. The paper also focuses on role of Biodiversity Management Committees (BMCs) on various aspects of Benefit Sharing, development of sustainable livelihood approach, etc.